2014
DOI: 10.3758/s13428-014-0528-1
|View full text |Cite
|
Sign up to set email alerts
|

childLex: a lexical database of German read by children

Abstract: This article introduces childLex, an online database of German read by children. childLex is based on a corpus of children's books and comprises 10 million words that were syntactically annotated and lemmatized. childLex reports linguistic norms for lexical, superlexical, and sublexical variables in three different age groups: 6-8 (grades 1-2), 9-10 (grades 3-4), and 11-12 years (grades 5-6). Here, we describe how childLex was collected and analyzed. In addition, we provide information about the distributions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
122
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 145 publications
(129 citation statements)
references
References 20 publications
1
122
0
6
Order By: Relevance
“…The item set contained 80 words, 80 pseudohomophones, and 80 nonwords (e.g., Hand, Hant, Hond, see the appendix for full item list) and 60 filler items. Forty short (three to five letters) and 40 long words (six to nine letters) with high frequency (mean absolute frequency of 1537.80 for 9-to 10-year-old children according to childLex corpus; Schroeder, Würzner, Heister, Geyken, & Kliegl, 2015) were selected. Pseudohomophones were derived from the words by exchanging one phonologically identical grapheme and nonwords were derived by exchanging one grapheme per syllable.…”
Section: Eye-tracking Paradigmmentioning
confidence: 99%
See 1 more Smart Citation
“…The item set contained 80 words, 80 pseudohomophones, and 80 nonwords (e.g., Hand, Hant, Hond, see the appendix for full item list) and 60 filler items. Forty short (three to five letters) and 40 long words (six to nine letters) with high frequency (mean absolute frequency of 1537.80 for 9-to 10-year-old children according to childLex corpus; Schroeder, Würzner, Heister, Geyken, & Kliegl, 2015) were selected. Pseudohomophones were derived from the words by exchanging one phonologically identical grapheme and nonwords were derived by exchanging one grapheme per syllable.…”
Section: Eye-tracking Paradigmmentioning
confidence: 99%
“…Pseudohomophones were derived from the words by exchanging one phonologically identical grapheme and nonwords were derived by exchanging one grapheme per syllable. Words, pseudohomophones, and nonwords were matched on number of letters, bigram-frequency, and trigram-frequency according to childLex (Schroeder et al, 2015). Item characteristics are shown in Table 2.…”
Section: Eye-tracking Paradigmmentioning
confidence: 99%
“…For comparison, we will also provide corresponding results from three existing nondevelopmental databases for (young) adults: the Dutch Lexicon Project (DLP; Keuleers, Diependaele, & Brysbaert, 2010), the British Lexicon Project (BLP; Keuleers et al, 2012), and the English Lexicon Project (ELP; Balota et al, 2007). Finally, we will compare the correlations between the RTs in different age groups and various frequency estimates derived from German corpora for adults (SUBTLEX-DE; see Brysbaert et al, 2011;CELEX, see Baayen, Piepenbrock, & Gulikers, 1995;and DWDS, see Geyken, 2007) and children (childLex; see Schroeder, Würzner, Heister, Geyken, & Kliegl, 2015).…”
Section: Theoretical Aims Of the Present Studymentioning
confidence: 99%
“…To ensure that all words are known even by children in Grade 2, we intentionally did not select words with very low frequencies (by inspecting corresponding adult norms), proper names, and words that are very specialized. After data collection, we compared the words in the DeveL sample to the frequencies of the childLex corpus (Schroeder et al, 2015). Results showed that we were successful in selecting words that were appropriate for primary school children, but not too infrequent: Overall, only three words of the DeveL subset were not included in childLex and only 11 words had normalized frequency values below 1/million.…”
Section: Stimulimentioning
confidence: 99%
See 1 more Smart Citation